Skrining Fitokimia Dan Evaluasi Sediaan Teh Celup Daun Kopi Arabika (Coffea arabica L) - Relin Yesika; Eka Desnita; Elsa Marsellinda; Revivo Rinda Pratama (Jurnal Ilmu Farmasi Terapan dan Kesehatan, 2026)
Arabica coffee (Coffea arabica L.) leaf has long been used in traditional medicine for enhancing stamina, promoting diuresis, and stimulating appetite. Arabica coffee leaves are known to contain diverse bioactive secondary metabolites that contribute to antibacterial, antioxidant, anti-inflammatory, antidiabetic, and antidyslipidaemic activities. This study aimed to evaluate the phytochemical profile and sensory characteristics of Arabica coffee leaf tea formulated in tea bags. Phytochemical screening was conducted, followed by product evaluation through organoleptic testing, pH and Sensory evaluation. Sensory evaluation involved 25 untrained panelists using questionnaire. Phytochemical analysis confirmed the presence of alkaloids, phenols, flavonoids, terpenoids, and tannins in the leaves coffea arabica leaf. Organoleptic assessment showed a distinctive aroma, brownish-orange color, clear infusion, and bitter taste. The tea infusion exhibited acidic properties, with an average pH of 5. Sensory analysis of color indicated that 60% of panelists expressed strong liking, while 40% reported liking. Aroma evaluation showed that 16% expressed strong liking, 60% liking, and 24% a neutral response. Taste evaluation: 20% expressed strong liking, 20% liking, 36% a neutral response, and 12% expressed dislike. In conclusion, Arabica coffee leaf tea preparations have the potential to be developed as a health-promoting beverage with various beneficial properties similar to Camellia sinensis.